Fabio De Sanctis : La Traversata delle alpi - Cortenova, Giorgio; Ivsic, Radovan; Le Brun, Annie (Roma : Officina Undici, 1972)
Cloth-hinged stiff board folder, with die-cut handle and pictorial label. Heavily illustrated with photographs by Umberto Santucci. Near fine. First edition. One of 2000 numbered copies. A visually rich monograph of this collaborative exhibition by the Italian surrealist sculptor. Cortenova's text is bound separately, in an inserted sleeve, and is accompanied by a folded copy of the exhibition poster
Italiaans
boek
Keywords: De Sanctis, Fabio